The Pattern of Education in Damascus (Examining Ibn Taymiyyah's Concept of Islamic Education) - Rian Hidayat; Nasution, Zubeir Ahmad; Riri Lovita (Journal of Practice Learning and Educational Development, 2025)
Islamic education has developed since the time of the Prophet PBUH with the revelation of the Qur'an, continued during the time of the Khulafaurrasyidin, and achieved significant progress during the Umayyad Dynasty. This study aims to examine the development of Islamic education during the Umayyad period in Damascus and Andalusia, focusing on the education system, the role of mosques, and the influence of Arabic culture. Using a literature research method with a qualitative approach, data is collected from primary sources such as books on the history of Islamic civilization by Samsul Munir Amin, Samruddin Nasution, and others, as well as secondary sources in the form of accredited journal articles. Content analysis was carried out to process data descriptively. The results of the study show that Islamic education during the Umayyad period focused not only on religious science, but also on secular sciences such as medicine, astronomy, and philosophy, which became the foundation of the progress of Islamic civilization. The mosque served as a center of learning, with Arabic as the main language, adopting the memorization tradition of the pre-Islamic Arabs enriched by the tradition of writing revelations. This education also serves to strengthen the social, political, and cultural identity of Muslims, supporting regional expansion and intellectual development.